Hubungan Antara Kecerdasaan Spiritual dengan Perilaku Merundung pada Remaja SMP Al Irsyad Cilacap - Trimeilia Suprihatiningsih; Dwi Maryanti; Ida Ariani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Bullying is a type of conduct disorder and antisocial behavior that makes the group of children with the largest mental disorder. Spiritual factors or religiosity are also associated with juvenile delinquency. The purpose of this study was to determine the relationship between spiritual intelligence and bullying behavior in adolescents at Al Irsyad Middle School, Cilacap. This research is a correlation research with cross sectional design. The sample in this study were students of class VIII and IX at SMP Al Irsyad Cilacap as many as 69 respondents. The sampling technique used was purposive sampling. Data analysis used univariate test to determine the frequency distribution of each variable and bivariate using the Spearman-rank test. The results showed that there was a significant relationship between spiritual intelligence and bullying behavior in students (p value 0.000).